Extremely violent societies : mass violence in the twentieth-century world - Gerlach, Christian 1963- (Cambridge Univ. Press, 2010)
"Violence is a fact of human life. This book trace the social roots of the extraordinary processes of human destruction involved in mass violence throughout the twentieth century. Christian Gerlach shows that terms such as 'genocide' and 'ethnic cleansing' are too narrow to explain the diverse motives and interests that cause violence to spread in varying forms and intensities from killings and expulsions to enforced hunger, collective rape, strategic bombing, forced labour and imprisonment. He explores what happened before, during, and after periods of wide-spread bloodshed in Armenia, Indonesia, Bangladesh, Greece and anti-guerilla wars in order to highlight the crucial role of socio-economic pressures in the generation of group conflicts. By focussing on why so many different people participated in or supported mass violence, and why different groups were victimized, the author offers us a new way of understanding one of the most disturbing phenomena of our times"--